The chemical history of lithography - Okoroanyanwu, Uzodinma (SPIE Press monograph, 2020)
"This volume is the first in a series of three books that make up the second edition of Chemistry and Lithography, which is continued in volume 2 (Chemistry in Lithography) and volume 3 (The Practice of Lithography). Each volume is a unit in itself and can stand alone, which is fortunate in view of their different subject matters. Volume 1 of the present edition weaves together threads of a narrative on the history of optical and molecular physics, optical technology, chemistry, and lithography, with a view to creating a rich tapestry that gives the reader new insights into an aspect of the relationships between these fields that are often not fully appreciated: how the marriage between chemistry and optics led to the development and evolution of lithography. We show how major developments in chemistry, physics and technology of light influenced the invention and development of lithography, well beyond what its inventor envisioned. We also show how developments in lithography have not only influenced the development of optics and chemistry, but also played a critical role in the large scale manufacture of integrated circuits that run the computers and machineries on which our modern electronic and information age depend. Part of the analysis in this volume is necessarily skewed towards the underlying science and technologies of advanced lithographic patterning techniques, in terms of materials, processes, imaging, along with their unique features, strengths and limitations. This book also provides an analysis of the emerging trends in lithographic patterning, along with the current and potential applications of the resulting patterned structures and surfaces"--